OPTIMIZING THE DISTRIBUTION OF ZAKAT, INFAQ, SHADAQA (ZIS) THROUGH THE BAZNAS PROGRAM ON PROSPERITY LEVELS IN BENGKALIS - Trisna Eka Sari; Seri Wahyuni; Riskiyatul Hasanah; Khaeqal Fitradinata (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Social prosperity is a priority scale in efforts to achieve national development. Until now, the country is still facing problems and difficulties in achieving social prosperity. The Bengkalis Regency said that there was a problem with the high number of people below the poverty line. He said that "the poverty rate in Bengkalis Regency continues to decline every year", "in 2010 it was 8.25%, then in 2022 it was 6.32%, or is in the sixth lowest position of the 12 districts/cities in Riau Province and below the Riau Province average of 6.84% and the national average of 9.57%.The Goal of this qualitative research is to collect data on the best way to optimize the distribution of Baznas zakat, infaq and Shadaqa towards the level of prosperity of ZIS mustahik in Bengkalis Regency. Research data was collected using integrated primary data from observation, documentation and interviews. Triangulation techniques are used to analyze the collected data, which includes adjustment, presentation, drawing conclusions, and verification. As a result, the distribution of Zakat, Infaq, Shadaqa (ZIS) by BAZNAS is very effective. This is because BAZNAS audits Bengkalis Regency's Baznas financial reports every year, and independent auditors are used to carry out the audit. By considering BAZNAS' extraordinary programs such as the Bengkalis Sejahtera Program, Bengkalis Smart Program, Bengkalis Healthy Program, Bengkalis Care Program, and Bengkalis Taqwa Program, it can be concluded that optimizing the distribution of zakat will have a big impact on the prosperity of mustahik in Bengkalis Regency.